STUDI LITERATUR: PENGARUH KEPEMIMPINAN ISLAMI TERHADAP KINERJA KARYAWAN BANK SYARIAH DI INDONESIA - Nur Ainia, Risna; Agung Prakoso, Firza; In, Churin (STEBI Global Mulia Cikarang, 2023)
This journal aims to analyze the relationship between Islamic leadership and the performance of Sharia Bank employees. This study is a qualitative descriptive study with a literary study method, namely a review of previous research relating to the relationship between Islamic leadership and the performance of Sharia Bank employees. Some data was obtained from research journals and previous scientific articles which were then analyzed by data display and data verification. The results of data analysis show that there are three previous studies which state that Islamic leadership has a positive effect on the performance of Sharia Bank employees. In two other studies, there were results that Islamic leadership did not have a significant positive effect on the performance of Sharia Bank employees. Keyword: Islamic Leadership, Kinerja Karyawan, Sharia Bank